Developing of content analysis of parenting model in the early postpartum period of predicting rejection of her infant - Suryani Manurung; Fenti Hasnani; Dewi Marianthi (Malahayati International Journal of Nursing and Health Science, 2021)
Background: Cases of abandoned babies recorded in Indonesia can be seen in people who abandon babies in public places. Recognizing maternal parenting can prevent this condition.Purpose: To develop of content analysis of parenting model in the early postpartum period of predicting rejection of her infantMethod: A qualitative design and activities to validate the contents of the statement items. The instrument is in the form of a questionnaire containing 42 statement items for acceptance statements and 34 for rejection statements with very appropriate, appropriate, and incorrect choices. Content analysis by panelists through expert judgment by providing a questionnaire instrument (logical validity). The analysis test is a content validity index (CVI) based on the level of agreement of six expert panelists (Survey-CVI).Results: CVI analysis obtained 21 statement items that describe acceptance with an average I-CVI (individual-CVI) of 0.84. The statement items that represent the baby's refusal are 29 items with an average I-CVI of 0.95.Conclusion: The early stages of the development of parenting models in predicting acceptance and rejection of infants in the postpartum period have resulted in a close CVI.